Congestion Management with Static Voltage Stability Index Approach Incorporated with SVC and TCSC Using Cat-Firefly Algorithm in Deregulated Power System - Jami Sridevi, V. Usha Rani (International Journal of Advanced Science and Technology, 2020)
In this research work  an apparent and cost-effective model for congestion management is designed using FACTS devices. The advent has a two-step procedure, initially, optimal placement of FACTS devices like Static VAR Compensator (SVC) and Thyristor Controlled Series Capacitor (TCSC) are proposed in the deregulated system network, Later control parameters are tuned optimally to their augment values. The formulated methods and constraints characterizes a multi-objective optimization problem. Hence a hybrid optimization algorithm influenced by the behaviour of Cat and firefly is deployed to adopt the optimal placement of TCSC and SVC with optimal tuning.  MATLAB simulation is performed on IEEE 30 bus test system to test the potency of the proposed model . Simulated results are later compared for distinctive conditions of Static voltage stability for congestion management in the deregulated network